2019
DOI: 10.1101/560037
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lytic bacteriophage have diverse indirect effects in a synthetic cross-feeding community

Abstract: Bacteriophage shape the composition and function of microbial communities. Yet, it remains difficult to predict the effect of phage on microbial interactions. Specifically, little is known about how phage influence mutualisms in networks of cross-feeding bacteria. We modeled the impacts of phage in a synthetic microbial community in which Escherichia coli and Salmonella enterica exchange essential metabolites. In this model, phage attack of either species was sufficient to inhibit both members of the mutualism… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 45 publications
(41 reference statements)
0
15
0
Order By: Relevance
“…To start, we modified a 201 resource-explicit model of the coculture that simulated the abundance of bacteria, phage, and 202 resources through time (Fig 4a) (Fazzino et al, 2020). We used model parameters informed by 203 literature values and used wet-lab experiments to measure maximum growth rates (Table S2, 204 Fig 4b), and confirmed that the model accurately simulated the growth dynamics of the phage-205 free coculture (Fig 4c) (Fazzino et al, 2020). Phage-resistant bacteria were seeded in at low 206 frequencies to approximate standing variation for phage resistance.…”
Section: Results 115mentioning
confidence: 99%
See 2 more Smart Citations
“…To start, we modified a 201 resource-explicit model of the coculture that simulated the abundance of bacteria, phage, and 202 resources through time (Fig 4a) (Fazzino et al, 2020). We used model parameters informed by 203 literature values and used wet-lab experiments to measure maximum growth rates (Table S2, 204 Fig 4b), and confirmed that the model accurately simulated the growth dynamics of the phage-205 free coculture (Fig 4c) (Fazzino et al, 2020). Phage-resistant bacteria were seeded in at low 206 frequencies to approximate standing variation for phage resistance.…”
Section: Results 115mentioning
confidence: 99%
“…To represent our cross-feeding microbial community, we modified a series of resource-explicit 403 ordinary differential equations to simulate an E. coli and S. enterica cross-feeding system in 404 which one species grows on nutrients secreted by the other (Fazzino et al, 2020). We used 405…”
Section: In Silico Modeling Of Communities 402mentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, we saw an increase in abundance of metabolically dependent S. enterica (11). A closer examination revealed a metabolic explanation: phage lysis released nutrients in the environment which the metabolic partner could then scavenge, reminiscent of the “viral shunt” which cycles nutrients in marine food webs (12).…”
Section: Perspectivementioning
confidence: 88%
“…Sequence analysis was performed using BreSeq (48) to align Illumina reads to reference E. coli and S. enterica genomes as previously described (49). Briefly, mutation lists for resistant populations were filtered such that variation between our ancestral strains and the reference genome were removed, as well as any mutations which also arose in the antibiotic-free populations.…”
Section: Sequencingmentioning
confidence: 99%